2009
DOI: 10.1002/app.29836
|View full text |Cite
|
Sign up to set email alerts
|

Melt rheology of aliphatic hyperbranched polyesters

Abstract: Rheological behavior in melt of aliphatic hyperbranched polyesters (AHBP), synthesized using pseudo-one-step and one-step procedure, was investigated in this work. Three commercially available AHBP were also examined. Because of the presence of relatively strong hydrogen bonds between numerous end hydroxyl groups, AHBP of lower generation number, as well as the sample of tenth pseudo generation, show non-Newtonian behavior in the entire investigated frequency and temperature region. However, for other examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
2
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 39 publications
6
20
2
3
Order By: Relevance
“…Since linear polymers show constant activation energies regardless of molar mass , the increase indicates an increasing extent of branching . The high values of the activation energies found are comparable to values of 174–215 kJ mol −1 reported for other branched polyesters . The authors explain that interactions of polar groups such as the OH and COOH end groups of the PET grades considered here can cause a more pronounced viscosity decrease at higher temperatures.…”
Section: Resultssupporting
confidence: 83%
“…Since linear polymers show constant activation energies regardless of molar mass , the increase indicates an increasing extent of branching . The high values of the activation energies found are comparable to values of 174–215 kJ mol −1 reported for other branched polyesters . The authors explain that interactions of polar groups such as the OH and COOH end groups of the PET grades considered here can cause a more pronounced viscosity decrease at higher temperatures.…”
Section: Resultssupporting
confidence: 83%
“…With increasing generation number, the behavior slowly approached a terminal behavior with G ″ ∼ ω 0.9 , i.e., close to the terminal scaling, whereas the scaling exponent for G ′ was around one. These results are in agreement with non‐terminal G ′ and G ″ scaling that was previously reported for dendritic polymers and for HB polyesters . These results indicate that synthesized HB polyesters exhibited slower relaxation modes compared with those for most linear polymers as a consequence of the high branch density and intermolecular interactions.…”
Section: Resultssupporting
confidence: 91%
“…It was observed that the values of the thermal coefficient of expansion, α f , and the fractional free volume, f g , increase with increasing size or pseudo‐generation of the HB polyesters due to the increasing freedom of movement of the existing branches. This trend was identical and the values of α f and f g were similar to those found earlier for other HB polyesters . Such a trend is in accordance with the observed decrease in E a with generation number and suggests that the flexibility is increased because the hydrogen bonding is less pronounced.…”
Section: Resultssupporting
confidence: 91%
“…The DSC curves of the synthesized PU samples obtained during the first and second heating runs are shown in Fig. 31 The T g values of the PUs synthesized in this work, determined during the second heating run, were in the range from 50 to 58 °C (Table II) content. The broad endothermic peak around 150 °C, observed in the DSC curves during the first heating run, corresponds to H-bond interactions in PU samples.…”
Section: Thermal Properties Of the Synthesized Polyurethane Networkmentioning
confidence: 83%